“Elas são feras na arte de driblar”: um estudo sobre as mulheres futebolistas no campo desportivo paraense - FONSECA, Bruna da Silva (2022)
The present work aims to analyze the difficulties faced in the practice of women's football in Pará. To this end, a case study was conducted within the premises of ESMAC, a women's team that has been standing out in the sports scenario of Pará, which even without investments, salaries and other factors that will be perceived during this research, is still a of the women's teams that have been presenting results in recent years. Methodologically, the case study was adopted, a qualitative approach is increased in order to bring greater veracity to the information provided here through the data collected from field interviews. The help of authors such as: Silva (2015); GUIMARÃES (2008); KNIJNIK and SOUZA; SCOTT (1995) and others dealing with the theme in question was fundamental in the construction of this research. The research data indicate that even if there are numerous difficulties in the development of the women's football modality in Pará, there is still hope that the sport will be valued.